Answer:
d
Step-by-step explanation:
Solution by substitution method
y=7x+8
∴y-7x=8
and y=x+20
∴y-x=20
Suppose,
-7x+y=8→(1)
and -x+y=20→(2)
Taking equation (1), we have
-7x+y=8
⇒y=7x+8→(3)
Putting y=7x+8 in equation (2), we get
-x + 7x + 8 = 20
6x = 20-8
6x = 12
x= 12 / 6
x = 2
substitute for x in equation (3)
y = 7(x) + 8
y = 7(2) + 8
y = 22
Subtract 7a from both sides giving you 10=-5a and divide everything by 5. This gives you a=-2
Answer:
Step-by-step explanation:
<u>The quotient of </u>
- 5/6÷ (-13/7) =
- 5/6×(-7/13) =
- - 35/78
Set up a proportion:
y = 35 when x = 7
y = ? when x = 10
To get x from 7 to 10, you have to multiply by
. Therefore, you do the same to 35, and you get:

And your answer is 50 :)
Answer: 169 more?
Step-by-step explanation: I multiplied 13x13 and got 169